THE EFFECT OF ONLINE FOOD DELIVERY SERVICES ON CONSUMER BEHAVIORAL INTENTIONS - Ahmad Farhans; Erlita Ridanasti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research explored the Special Region of Yogyakarta towards online food delivery services, which had become a prominent trend within the food and beverage industry. Consumers were increasingly opting for the convenience of ordering food online rather than traditional dining out or takeout. This study aimed to develop an integrated model to examine the relationship between several antecedents (perceived ease of use, time-saving orientation, convenience motivation, privacy and security, and behavioral intention) and repurchase intention towards OFD services. The findings revealed that time-saving orientation, convenience motivation, and privacy and security positively influenced behavioral and repurchase intentions. These results offered valuable insights for OFD service providers and researchers, shedding light on the key factors driving urbanites to adopt and continue using these services.